1987
DOI: 10.3382/ps.0660341
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy of Thin and Soft Shells Induced by Feeding Calcium-Deficient or Vitamin D-Deficient Diets to Laying Hens

Abstract: A scanning electron microscopic study was conducted on shells from eggs laid by four groups of hens maintained on different types of diets: a) control, b) vitamin D3-deficient, c) Ca-deficient, and d) vitamin D3-deficient supplemented with 1,25-(OH)2D3. After 1 week for Ca-deficient hens and after 4 weeks for vitamin D3-deficient hens, the thickness of the shell decreased abruptly and numerous thin-shelled and soft-shelled eggs were laid. The study showed that with both Ca-deficient and vitamin D3-deficient di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…This effect would account for the improved egg specific gravity seen at 1,500 ICU D3/kg but not at 1,000 ICU D3/kg. Using scanning electron microscopy, Narbaitz et al (1987) reported that eggshells from hens fed a vitamin D3 deficient diet (0 ICU D3/kg) supplemented with l,25-(OH)2 D3 were ultrastructurally indistinguishable from eggs laid by hens fed the control level of vitamin D3.…”
Section: Variablementioning
confidence: 99%
“…This effect would account for the improved egg specific gravity seen at 1,500 ICU D3/kg but not at 1,000 ICU D3/kg. Using scanning electron microscopy, Narbaitz et al (1987) reported that eggshells from hens fed a vitamin D3 deficient diet (0 ICU D3/kg) supplemented with l,25-(OH)2 D3 were ultrastructurally indistinguishable from eggs laid by hens fed the control level of vitamin D3.…”
Section: Variablementioning
confidence: 99%
“…Bar and coworkers (Bar et al, 1984;Bar and Hurwitz, 1987) have shown that plasma l,25(OH) 2 D 3 was greater in laying hens with good egg shell quality and was reduced with age. Recently Narbaitz et al (1987) have shown that feeding l,25(OH) 2 D 3 to hens results in no abnormal changes in ultrastructural development of egg shells. It is also clear that level is critical when feeding D 3 metabolites, as toxic effects can be seen with as little as 7 to 10 |xg 1,25(OH) 2 D 3 /kg diet Soares et al, 1983).…”
Section: Introductionmentioning
confidence: 98%
“…The outer layers of the shell may be reduced or absent, but the inner mammillary layer is always present, suggesting that the hens stop laying before Ca concentrations in blood become too low for the formation of the mammillary knobs. Uncalcified portions of the shell organic matrix are not found, suggesting that Ca deposition and matrix formation are inhibited simultaneously (Narbaitz et al, 1987). Withdrawal of cholecalciferol from a layer diet drastically reduced blood 25(OH)D 3 , 1,25(OH) 2 D 3 and egg specific gravity within two weeks, which was followed by a decrease in blood total Ca.…”
Section: Vitamin D 3 (Cholecalciferol)mentioning
confidence: 95%